Acetylcholine Receptor and Muscle-Specific Kinase Autoantibodies - Huda, S; Vincent, A (2013)
Antibodies to the acetylcholine receptor are the principal pathogenic cause of myasthenia gravis. The disease results in fatigable muscle weakness that can affect the extraocular, proximal, bulbar, and respiratory musculature. The antibodies cause a reduction in acetylcholine receptors at the postsynaptic neuromuscular junction, resulting in defective neuromuscular transmission. They are mostly detected using the robust radioimmunoprecipitation assay, although other methods have recently been developed. In addition, there are more sensitive methods that are not yet commercially available. A subset of patients with myasthenia gravis do not have antibodies against acetylcholine receptors but instead have antibodies directed against muscle-specific kinase, another important postsynaptic neuromuscular junction protein. These antibodies can be measured by the same techniques, and the test is an important addition for the routine diagnostic laboratory. © 2014 Elsevier B.V. All rights reserved..